Effect of Aluminium Oxide Nanoparticles Suspended in Different Eg-Base Ratio to Enhanced Thermal Conductivity - N. A., Usri; Azmi, W. H.; R., Mamat; Khamisah, Abdul Hamid; G., Najafi (2015)

(untitled)
Thermal conductivity evaluation is important properties in order to enhance the ability of thermal fluid to work in a system. Nanoparticle suspended in a base fluid or known as nanofluids among researcher propagates positive enhancement compare to conventional base fluid. This paper conduct measurement of thermal conductivity using KD2 Pro Thermal properties Analyzer of different base ratio water to ethylene glycol based nanofluids. Nanoparticles Al2O3 is dispersed in 60:40, 50:50 and 40:60 volume percentage ratio of mixture base (water: ethylene glycol). The measurements is conducted for volume concentration range 0.2 < ϕ < 0.8 % at temperature of 30 to 70 oC. It was found that the thermal conductivity of the nanofluids enhanced with increment of volume concentration and temperature for all base ratio. The highest thermal conductivity enhancement of Al2O3 nanofluid is observed at volume concentration of 0.8 % for temperature 70 oC by 14.1 %. This paper concluded by providing equation to estimate thermal conductivity for designated ratio base.